Ejaculate Oxidative Stress Is Related with Sperm DNA Fragmentation and Round Cells - Valeria Maria Iommiello; Elena Albani; Alessandra Di Rosa; Alessandra Marras; Francesca Menduni; Giovanna Morreale; Shanti Lia Levi; Benedetta Pisano; Paolo Emanuele Levi-Setti (International Journal of Endocrinology)
Oxidative stress (OS) plays an essential role in male infertility aetiology by affecting sperm quality, function, and also the integrity of sperm DNA. The assessment of oxidative stress in semen may be an important tool to improve the evaluation of sperm reproductive capacity. The purpose of this study was the evaluation of any possible relation between the unbalance of oxidative stress caused by superoxide anion in the ejaculate with the presence of sperm DNA fragmentation and high concentration of round cells. 56 semen samples from males from couples suffering from infertility were evaluated according to World Health Organisation (WHO) 2010 guidelines. Oxidative stress levels from N1 (low) to N4 (high) were assessed in ejaculates using oxiSperm; DFI (sperm DNA fragmentation index) as assessed by the SCSA (Sperm Chromatin Structure Assay) was used for evaluation of sperm chromatin integrity. Our data show that high oxidative stress (N3-N4 levels) correlated positively with a DFI≥30% (P=0.0379) and round cells ≥1.500.000/mL (P=0.0084). In conclusion, OS increases sperm DNA damage. Thus evaluation of semen OS extent of sperm DNA damage in infertile man could be useful to develop new therapeutic strategies and improve success of assisted reproduction techniques (ART).